2007
DOI: 10.1007/s10495-007-0060-1
|View full text |Cite
|
Sign up to set email alerts
|

hCG treatment raises H2O2 levels and induces germ cell apoptosis in rat testis

Abstract: The clinical significance of exogenous hCG treatment is to stimulate steroidogenesis and spermatogenesis in the testis. However, the pathogenesis of detrimental effects on the testis arising out of chronic hCG treatment is yet to be clearly ascertained. In the present study we have shown that hCG treatment (100 IU/day) to rats for 30 days raises testicular oxidative stress leading to germ cell apoptosis and impairment of spermatogenesis. The treatment raises testicular H(2)O(2) levels along with increase in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 45 publications
(49 reference statements)
0
24
0
Order By: Relevance
“…Various environmental factors such as elevated scrotal temperature and oxidative stress have been linked to abnormal spermatogenesis and infertility (Anderson et al 1983, Emanuele & Emanuele 1998, Lue et al 2000, Rockett et al 2001, Dare et al 2002, Agarwal et al 2003, Aitken & Baker 2006, Gautam et al 2007, Aitken & Roman 2009, Shiraishi et al 2010 Figure 5 SUMO1 localizes to H 2 O 2 -induced DNA double-strand breaks in meiotic spermatocytes. Control (A 1 -A 4 ) and H 2 O 2 -treated (100 mM, 20 min B 1 -B 4 ) spermatocytes were co-immunolabeled using anti-gH2AX (red) and anti-SUMO1 (green) antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Various environmental factors such as elevated scrotal temperature and oxidative stress have been linked to abnormal spermatogenesis and infertility (Anderson et al 1983, Emanuele & Emanuele 1998, Lue et al 2000, Rockett et al 2001, Dare et al 2002, Agarwal et al 2003, Aitken & Baker 2006, Gautam et al 2007, Aitken & Roman 2009, Shiraishi et al 2010 Figure 5 SUMO1 localizes to H 2 O 2 -induced DNA double-strand breaks in meiotic spermatocytes. Control (A 1 -A 4 ) and H 2 O 2 -treated (100 mM, 20 min B 1 -B 4 ) spermatocytes were co-immunolabeled using anti-gH2AX (red) and anti-SUMO1 (green) antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…95 Interestingly, over-stimulation of the Leydig cells by chronic exposure to hCG (100 IU/day for 30 days in rats) also stimulates high levels of ROS production from these cells, that in turn stimulate lipid peroxidation, reduction in antioxidant enzyme activities, germ cell apoptosis and the consequential disruption of spermatogenesis. 98 Thus, as we saw with the involvement of the thyroid gland in the control of testicular function, a stable redox environment depends on an appropriately balanced gonadotrophic support, either hyper-or hypo-gonadotrophism will induce a state of oxidative stress in the testis.…”
Section: Disruption Of the Antioxidant Status Of The Testesmentioning
confidence: 96%
“…The use of hCG is reported to have noxious effects which can lead to male infertility due to impaired spermatogenesis because of an increase in free oxygen radicals [2, 22]. To the best of our knowledge, no other studies in the literature have studied the effects of hCG treatment on prolidase activity, oxidative stress, and antioxidant enzyme levels in the testes and penile tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Gautam et al [2] reported an increase in apoptosis in testicular germ cells and associated this with high oxidative stress and H 2 O 2 which is a sign of low antioxidant activity. Ozbek et al [26] found a significant increase in the number of giant cells and degenerated and desquamated cells in a testicular ischemia/reperfusion injury model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation